THE IMPORTANCE OF HEALTHCARE WORKERS’ EDUCATION FOR THE DETECTION OF WOMEN SURVIVORS OF GENDER-BASED VIOLENCE - Knezevic, Snezana (HEALTH CARE, 2020)
Introduction/Aim: Domestic violence is any form of gender-based violence that may result in the physical, psychological or sexual injury of a woman. The aim of the study was to determine whether there is a difference in attitudes between male and female healthcare workers about the importance of detecting women who have survived gender-based violence. Methods: Within this cross-sectional study, data were collected with the help of an anonymous, online questionnaire, from 78 healthcare providers (response rate 72.9) who were educated about the importance of identifying women survivors of gender-based violence. Results: Of 78 health workers, 14.1% were men and 85.9% were women. There was no significant difference between men and women in relation to their demographic characteristics (age, marital status, length of service and level of education). Men claimed significantly more often, compared to women, that the lack of staff was a key reason why institutional barriers made it impossible to provide assistance in the situation of gender-based violence. There was no significant difference between men and female professionals in relation to their attitudes towards other institutional, as well as social and personal barriers that made it impossible to provide assistance. Both men and women pointed out the following social barriers: low socio-economic status of patients (74.4%), understanding of the cultural environment, where the person who experienced the violence lived (60.2%), and social stereotypes and prejudice (59.0%), whereas the institutional barrier was the heavy workload (69.2%), and personal barriers were the time constraint in performing daily work (70.5%) and the limited authority of healthcare professionals (52.6%). Male healthcare workers claimed more often that violence was not reported because women who had suffered it had to return to the same environment and because women were ashamed and afraid of being condemned by the environment, while female health professionals believed that women were afraid of violence recurrence (68.7%). Conclusion: Education of health workers is crucial for acquiring knowledge and skills about genderbased violence that will enable them to help women who have survived it. Also, it is necessary to include more male professionals in this kind of education.